Jesus in the Jewish world - Vermès, Géza (SCM Press, 2010)
Readers of the present volume are offered lively and often humorous accounts of the impact of Jesus the Jew on Christian and Jewish readers; of the value of Josephus as a historical source regarding John the Baptist, James the brother of the Lord, and Jesus; the historical implications of ancient Jewish biblical exegesis; of the inside story of the monumental recasting by Vermes and his friends of Emil Schürer's History of the Jewish people; and of the sacrifice of Isaac and the story of the first-century Galilean rabbi, Hanina ben Dosa. The final two essays, written in 2007 and 2010, are particularly noteworthy, the first propounding a fresh and revolutionary approach to methodology in the study of the historical Jesus and the second restating and reinforcing Vermes's stance in the half-a-century long Son of Man debate